Analisis Literatur Pengaruh Suplementasi Viterna dalam Ransum terhadap Pertumbuhan Ternak Babi - Panji Lakiu (Fakultas Ekonomi Universitas KristenTentena, 2025)
Feed costs account for 60% to 80% of total pig production expenses, yet their utilization is often inefficient or hindered by the low quality of waste-based feeds characterized by high crude fiber content. This study aims to analyze the impact of Viterna supplementation on Average Daily Gain (ADG), evaluate its effectiveness in enhancing appetite and feed conversion efficiency, and provide a reference for the optimal supplementation dosage. The method employed is a literature review with a qualitative descriptive approach using content and comparative analysis of various secondary data from experimental research results. The results indicate that Viterna contains instant nutrients capable of accelerating growth and shortening harvest time from 10-12 months to 5-6 months. Supplementation is proven to increase palatability and feed efficiency through the stimulation of digestive enzymes. A daily dose of 5 cc is identified as the most optimal level for achieving maximum growth in the grower phase. In conclusion, Viterna administration effectively enhances biological productivity, overcomes the limitations of low-quality traditional feed, and improves the farm's environmental health by significantly reducing manure odor.